Кандагар. Последний приказ капитана: [роман] / Андрей Кавун, Олег Кавун, Андрей Орлов - Кавун Андрей Олегович (Олимп, 2010)
Экземпляры: ЦБ (20181018) / Инвентарный номер: 56564 / Цена: 50.00 / Сис.шифр: Р2 / Авт.знак: К12 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6